2022
DOI: 10.20944/preprints202208.0536.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of Bay of Bengal Extremely Severe Cyclonic Storm "Fani” Using Moving Nested Domain

Abstract: The prediction of an extremely severe cyclonic storm (ESCS) is one of the challenging issues due to increasing intensity and its life period. In this study, an ESCS Fani that developed over Bay of Bengal region during 27 April - 4May, 2019 and made landfall over Odisha coast of India is investigated to forecast the storm track, intensity and structure. Two numerical experiments (changing two air-sea flux parameterization schemes; namely FLUX-1 and FLUX-2) are conducted with the Advanced Research version of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Singh et al [17] reported an evaluation of the model for forecasting exceptionally severe cyclonic storms in the Bay of Bengal area. Tian et al [18] used a CNN model for tropical storm strength estimation using satellite remote sensing data.…”
Section: Related Workmentioning
confidence: 99%
“…Singh et al [17] reported an evaluation of the model for forecasting exceptionally severe cyclonic storms in the Bay of Bengal area. Tian et al [18] used a CNN model for tropical storm strength estimation using satellite remote sensing data.…”
Section: Related Workmentioning
confidence: 99%
“…In the last two decades, the forecast accuracy of TCs has increased by using high-resolution regional and global numerical weather prediction models [12][13][14][15][16] and improved and proper representations of physical parameterization schemes [17][18][19][20][21][22]. Additionally, TC forecast accuracy has improved by using advanced data assimilation techniques such as 3D/4D variational techniques, hybrid, and ensemble methods [5,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Previous studies have indicated that track forecasts improved, but intensity forecasts are still limited.…”
Section: Introductionmentioning
confidence: 99%